Osteoarthritis management: Does the pharmacist play a role in bridging the gap between what patients actually know and what they ought to know? Insights from a national online survey - Andrew J. McLachlan; Peter R. Carroll; David J. Hunter; Tom A. N. Wakefield; Rodney Stosic (Wiley, 2022)
Abstract Background Guidelines encourage engagement in self‐care activities for osteoarthritis (OA), but there are gaps in consumers' knowledge about suitable choices for self‐care. Community pharmacists are in an ideal position to contribute to OA management through screening and supporting evidence‐based pain management choices. Prior research established an association between health literacy and advice‐seeking and appropriateness of analgesics choices (both lower in participants with limited health literacy) amongst people living with OA. This article explores the implications of these data for pharmacists in OA management. Methods A national online survey was conducted amongst 628 adults aged 45-74 years, currently residing in Australia, with self‐reported symptoms of OA. All data were collected using a customized online questionnaire, which was completed only once. 'Self‐reported symptoms of OA' was based on six validated screening questions to identify people with OA without a formal clinical diagnosis. Results Respondents matched the typical profile of people diagnosed with OA; more than half were female (56%), knees (59%) and hips (31%) were the primary affected joints and 74% were either overweight or obese. Self‐identification of OA was limited (41%). Overall, 38% self‐managed their pain, and limited health literacy was associated with less advice‐seeking. Efficacy and ease of use were the main reasons cited for prompting use across all classes of nonprescription analgesic, with less than 20% reporting recommendation from a pharmacist. Participants were managing their pain with an average of 1.74 (95% confidence interval: 1.60-1.88) analgesics, but 73% reported inadequate pain relief and 54% had disrupted sleep. Conclusion Our findings highlight three key themes: lack of self‐identification of OA, suboptimal pain relief and limited use of the community pharmacist as a source of management advice. Equipping community pharmacists with tools to identify OA could bridge this gap. More research is needed to determine if it will improve consumers' ability to appropriately manage OA pain. Patient or Public Contribution Consumers living with OA contributed to the study outcomes, reviewed the survey questionnaire for face validity and advised on plain language terminology.